Design and Development of a Desktop-Based Cashier Application at the Legowo Satay Restaurant - Nila Nur'alifah; Suhartini; Muchlis (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
The advancement of information technology encourages various business sectors to adapt, including in managing sales transactions. Resto Sate Legowo, as a local culinary business, still relies on manual recording for cashier operations, which is prone to errors and takes considerable time. To address this issue, this study aims to design and develop a desktop-based cashier application to help accelerate and simplify the transaction process at Resto Sate Legowo. The development method used in this system is Rapid Application Development (RAD), with Unified Modeling Language (UML) as the design tool. This method allows for faster development by actively involving users in each stage of the process. The application is built using the Java programming language and MySQL as the database to store transaction and menu data. The result of this study is a cashier application capable of recording sales transactions, printing receipts, and generating daily reports automatically. System testing shows that the application functions properly and provides convenience for staff in managing transactions. With this application, it is expected that operational efficiency at Resto Sate Legowo can be significantly improved.